2015
DOI: 10.1002/ejhf.401
|View full text |Cite
|
Sign up to set email alerts
|

Which heart failure patients profit from natriuretic peptide guided therapy? A meta‐analysis from individual patient data of randomized trials

Abstract: AimsPrevious analyses suggest that heart failure (HF) therapy guided by (N-terminal pro-)brain natriuretic peptide (NT-proBNP) might be dependent on left ventricular ejection fraction, age and co-morbidities, but the reasons remain unclear. ..................................................................................................................................................................... Methods and resultsTo determine interactions between (NT-pro)BNP-guided therapy and HF with reduced [eje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 34 publications
5
93
0
2
Order By: Relevance
“…For the subgroup analyses, the HRs and associated 95% confidence intervals (CIs) for the interaction effect were derived from the subgroup-specific HRs with 95% CIs. Stratum-specific treatment effects for all-cause mortality (age and type of HF) and HF-specific admission (type of HF) were available from a previous IPD meta-analysis 33 that included seven RCTs. Interactions were calculated and pooled as an aggregate estimate with additional trials which had contributed IPD for this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the subgroup analyses, the HRs and associated 95% confidence intervals (CIs) for the interaction effect were derived from the subgroup-specific HRs with 95% CIs. Stratum-specific treatment effects for all-cause mortality (age and type of HF) and HF-specific admission (type of HF) were available from a previous IPD meta-analysis 33 that included seven RCTs. Interactions were calculated and pooled as an aggregate estimate with additional trials which had contributed IPD for this study.…”
Section: Discussionmentioning
confidence: 99%
“…We initially asked for the data for the RCTs included in their meta-analysis, allowing us to carry out the analyses; then we proposed that they should do the analyses to our analysis plan; tried to reach a compromise over the proposed analyses (with them doing the analyses); and asked for the pooled estimates from subgroup analyses that had already been carried out. 51 None of these proposals was successful and, therefore, we were unable to obtain IPD, or the results of subgroup analyses, from most RCTs included in the IPD meta-analysis by Troughton et al 25,33 Consequently, we were unable to perform the subgroup analyses specified in the protocol. 35 Other changes to the study from the protocol stage include:…”
Section: Checking For Publication and Data Availability Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…95 Another meta-analyses of individual patient data sought to investigate the interactions between age, comorbidities, or type of HF (preserved or reduced LVEF) and treatment response in the randomized trials of (NT-pro) BNP-guided therapy in HF. 96 These authors concluded that the benefits of therapy guided by (NT-pro) BNP were present in HFrEF only. However, most investigators agree that the ongoing Guiding Evidence Based Therapy Using Biomarker Intensified Treatment in Heart Failure (GUIDE-IT) trial (Table 2) will help clarify this important question.…”
Section: Biomarkers and Risk Prediction Modelsmentioning
confidence: 99%
“…3 In this issue of the journal, D'Elia et al discuss the role of new biomarkers for phenotyping these patients and differentiate pathogenetic mechanisms. 4 Other studies regard the independent prognostic role of high sensitivity troponin T measurements and their changes in patients with acute HF, 5 the use of biomarkers to select the HF patients at low risk of events, 6 the selection of the patients more likely to benefit from natriuretic peptides guided therapy 7 and a new, and first, marker of muscle wasting. 8 With respect of treatment, a simple treatment of sleep disordered breathing, based on a lateral sleep position, is shown to be effective in patients with HF, above all when obstructive sleep apnea is their main complaint.…”
mentioning
confidence: 99%